PODPORZĄDKOWANIE PRACOWNIKA PRACODAWCY W ASPEKCIE CZASU PRACY – WYBRANE PROBLEMY - Duraj, Tomasz (Zeszyty Prawnicze, 2016)
THE EMPLOYEE’S SUBORDINATION TO THE EMPLOYERAS REGARDS WORKING HOURS. SELECTED PROBLEMS Summary The subject of this paper is a description of the characteristic features of an employee’s subordination to his employer as regards working hours. An employer’s management rights in this respect are particularly relevant as regards the efficiency of the employee’s work and reduce the risk that any defective work on the employee’s part could mean for the employer. The author analyses the management rights of employers relating to factors contributing to the organisation of working hours such as the standard, extent, system, and schedule of working hours. His deliberations on these issues show that an employer’s rights pertaining to unilateral determination of working hours are in fact restricted. This is so because usually the system or schedule of working hours tends to be established in the context of a collective employment system or set of rules, in other words the employer’s freedom to make decisions is limited since he is obliged to cooperate with the trade unions active in his company or business. The widest scope of rights employers enjoy as regards the organisation of working hours concerns the right to order employees to work overtime and unscheduled time (but with consideration of any hours of duty on a rota system or duty travel); and as regards the compilation of detailed timetables of working hours.